2005
DOI: 10.1602/neurorx.2.3.513
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of focal dystonia

Abstract: Summary: Animal models indicate that the abnormal movements of focal dystonia result from disordered sensorimotor integration. Sensorimotor integration involves a comparison of sensory information resulting from a movement with the sensory information expected from the movement. Unanticipated sensory signals identified by sensorimotor processing serve as signals to modify the ongoing movement or the planning for subsequent movements. Normally, this process is an effective mechanism to modify neural commands fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 169 publications
(170 reference statements)
0
8
0
Order By: Relevance
“…However, these alterations may also in some circumstances, such as after an injury or the sustained performance of repetitive muscular activity, become maladaptive plastic changes that are thought to be responsible for initiating and perpetuating certain movement disorders and chronic pain syndromes. 24,[39][40][41][42][43][44][45][46][47][48][49][50][51] Furthermore, joint dysfunction originating from an injury may be a cause of ongoing pain and loss of function due to maladaptive sensorimotor integration from a hyperafferentiation of the CNS from the dysfunctional joints and associated structures. [52][53][54][55][56][57][58] Does Repetitive Muscular Activity and Joint Dysfunction Lead to Maladaptive Plasticity?…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…However, these alterations may also in some circumstances, such as after an injury or the sustained performance of repetitive muscular activity, become maladaptive plastic changes that are thought to be responsible for initiating and perpetuating certain movement disorders and chronic pain syndromes. 24,[39][40][41][42][43][44][45][46][47][48][49][50][51] Furthermore, joint dysfunction originating from an injury may be a cause of ongoing pain and loss of function due to maladaptive sensorimotor integration from a hyperafferentiation of the CNS from the dysfunctional joints and associated structures. [52][53][54][55][56][57][58] Does Repetitive Muscular Activity and Joint Dysfunction Lead to Maladaptive Plasticity?…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…Dystonia might be due to basal ganglia dysfunction associated with globus pallidus interna hypoactivation and cortical overactivation 7. Basso and colleages revealed that reduced basal ganglia dopamine levels causes a decrease in nucleus raphe magnus inhibition of the blink circuit that increases trigeminal blink excitability 8…”
Section: Discussionmentioning
confidence: 99%
“…Focal dystonia can be experimentally induced in animals ( 65 ) and cases of focal muscle contractions in domestic animals may resemble human focal dystonia. Meyer-Lindenberg et al ( 66 ) described an interesting case of severe bilateral blepharospasm in a Great Dane dog.…”
Section: Hyperkinetic Movement Disorders In Domestic Animals: Common mentioning
confidence: 99%